2017
DOI: 10.1016/j.stemcr.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Human Pluripotent Stem Cell Microglia Model Displays a Neuronal-Co-culture-Specific Expression Profile and Inflammatory Response

Abstract: SummaryMicroglia are increasingly implicated in brain pathology, particularly neurodegenerative disease, with many genes implicated in Alzheimer's, Parkinson's, and motor neuron disease expressed in microglia. There is, therefore, a need for authentic, efficient in vitro models to study human microglial pathological mechanisms. Microglia originate from the yolk sac as MYB-independent macrophages, migrating into the developing brain to complete differentiation. Here, we recapitulate microglial ontogeny by highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
578
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 441 publications
(612 citation statements)
references
References 47 publications
29
578
5
Order By: Relevance
“…20 We also have performed RNA-sequencing of myeloid progenitors (CD34 + CD43 + CD45 + CD18 + ) harvested during progressive commitment and maturation to IPSDM 8 and showed that the expression profile of those progenitors is highly correlated to that of IPSDM but not CD14 + monocytes (Figure 2). Thus, successful differentiation of circulating monocytes will rely on a more complete understanding of mechanisms regulating definitive hematopoietic specification 24 and identification of factors governing the generation of HSCs from iPSC, 25 knowledge gaps that remain major goals of regenerative medicine.…”
Section: Generation Functional Feature and Molecular Profiling Of Ipsdmmentioning
confidence: 99%
See 1 more Smart Citation
“…20 We also have performed RNA-sequencing of myeloid progenitors (CD34 + CD43 + CD45 + CD18 + ) harvested during progressive commitment and maturation to IPSDM 8 and showed that the expression profile of those progenitors is highly correlated to that of IPSDM but not CD14 + monocytes (Figure 2). Thus, successful differentiation of circulating monocytes will rely on a more complete understanding of mechanisms regulating definitive hematopoietic specification 24 and identification of factors governing the generation of HSCs from iPSC, 25 knowledge gaps that remain major goals of regenerative medicine.…”
Section: Generation Functional Feature and Molecular Profiling Of Ipsdmmentioning
confidence: 99%
“…Thus, IPSDM may developmentally relate to and be a good model for MYB -independent tissue resident macrophages. Indeed, several iPSC to microglia-like cell differentiation protocols were published this year using cytokines representing the main driver of microglia lineage, 18, 19 co-culture with iPSC-derived neurons 20, 21 and astrocytes, 22 or incubating with cytokines derived from those cell types 23 to recapitulate organ-specific cues. Takata et al has established a protocol that specifically resembles primitive hematopoiesis and YS macrophages for further differentiation into tissue macrophage-like cells by co-culture or engraftment.…”
Section: Generation Functional Feature and Molecular Profiling Of Ipsdmmentioning
confidence: 99%
“…Activated hiPSC-derived microglia, cocultured with hiPSC-derived cortical neurons, have been shown to exhibit more physiologically correct behaviors than monoculture controls. These behaviors include the downregulation of pathogen response pathways and a more anti-inflammatory cytokine-based response [Haenseler et al, 2017]. Methods for producing myelinating oligodendrocytes from hiPSC are also available [Wang et al, 2013;Ehrlich et al, 2017].…”
Section: Complexitymentioning
confidence: 99%
“…Although cocultures of hiPSC-derived neurons with microglia have been reported [Haenseler et al, 2017], their ability to faithfully recapitulate inflammatory responses within in vitro models has yet to be demonstrated. Neuroinflammation is a hallmark of AD and neurodegenerative diseases in general [Heneka et al, 2015;Walters et al, 2016].…”
Section: Future Directionsmentioning
confidence: 99%
“…Investigations of typical microglial cells are limited in vitro, because the source of this cell population in the brain is, as widely accepted, the yolk sac releasing a wave of primitive macrophages as progenitor cells of microglia during the early embryonal development [21] [22] [23] [24]. Microglial population colonizes the whole CNS and maintains itself by local proliferation [23] [24].…”
Section: Introductionmentioning
confidence: 99%